No Clear Effect of Initiating Vaccination against Common Endemic Infections on the Amounts of Prescribed Antimicrobials for Danish Weaner and Finishing Pigs during 2007–2013 - Kruse, Amanda Brinch; de Knegt, Leonardo Víctor; Nielsen, Liza Rosenbaum; Alban, Lis (Frontiers in Veterinary Science, 2017)
It is often stated that vaccines may help reduce antimicrobial use in swine production. However, limited evidence is available outside clinical trials. We studied the change in amounts of antimicrobials prescribed for weaners and finishers in herds following initiation of vaccination against five common endemic infections: Mycoplasma hyopneumoniae, Actinobacillus pleuropneumoniae, Porcine Circovirus Type II, Porcine Reproductive and Respiratory Syndrome virus and Lawsonia intracellularis. Comparison was made to the change after a randomly selected date in herds not vaccinating against each of the infections. Danish sow herds initiating vaccination during 2007-2013 were included (69-334 herds, depending on the analysis). Danish sow herds with no use of the vaccine in question were included as non-exposed herds (130-570 herds, depending on the analysis). Antimicrobial prescriptions for weaners in sow herds and for finishers in receiving herds were extracted from the VetStat database for a period of 12 months before and 6-18 months after the first purchase of vaccine, or random date and quantified as average animal daily doses (ADD) per 100 animals/day. The herd-level difference between ADD in the period after and before-vaccination was the outcome in linear regression models for weaner pigs, and linear mixed effects models for finishing pigs, taking into account sow herds delivering pigs to two or more finisher herds. Three plausible risk factors (Baseline ADD, purchase of specific vaccine, purchase of other vaccines) and five confounders (herd size, export and herd health status, year and season) were initially included into all 10 models. The main significant effect in all models was the Baseline ADD; the higher the Baseline ADD was for weaner and finishing pigs, the larger the decrease in ADD was following vaccination (or random date for non-vaccinating herds). Regardless of vaccination status, almost equal proportions of herds experienced a decrease and an increase in ADD resulting in no overall change in ADD. Furthermore, only minor effects were found, when vaccinations were used in combination. In conclusion, this study provided little support for the hypothesis that vaccination against five common endemic diseases provides a plausible general strategy to reduce antimicrobial use in Danish pig herds.